2014
DOI: 10.4062/biomolther.2014.006
|View full text |Cite
|
Sign up to set email alerts
|

The Polyphenol Chlorogenic Acid Attenuates UVB-mediated Oxidative Stress in Human HaCaT Keratinocytes

Abstract: We investigated the protective effects of chlorogenic acid (CGA), a polyphenol compound, on oxidative damage induced by UVB exposure on human HaCaT cells. In a cell-free system, CGA scavenged 1,1-diphenyl-2-picrylhydrazyl radicals, superoxide anions, hydroxyl radicals, and intracellular reactive oxygen species (ROS) generated by hydrogen peroxide and ultraviolet B (UVB). Furthermore, CGA absorbed electromagnetic radiation in the UVB range (280–320 nm). UVB exposure resulted in damage to cellular DNA, as demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 44 publications
2
73
0
1
Order By: Relevance
“…Kumar et al [79] found that a combination of ellagic acid with curcumin (25 μM each) caused SBs while the separate compounds had no significant effect. A decrease in (background) SBs with epigallocatechin gallate or epicatechin gallate was reported by Durgo et al [36] at 48 but not 72 h. At more reasonable concentrations, the results are mixed: decreases in UV(B)-induced SBs [70] and cyclobutane pyrimidine dimers [72]; decreases in H 2 O 2 -induced SBs and MN [74]; a decrease in SBs induced by cumene hydroperoxide [75]; but SBs and Fpg-sites increased in tetradecanoyl phorbol acetate (TPA)-stimulated neutrophils [78] and an increase in SBs with ellagic acid in prostate cancer cells was reported by Vanella et al [73] at concentrations of 9 μM in one of the cell lines but higher concentrations in two other lines.…”
Section: Isolated Phytochemicalsmentioning
confidence: 84%
“…Kumar et al [79] found that a combination of ellagic acid with curcumin (25 μM each) caused SBs while the separate compounds had no significant effect. A decrease in (background) SBs with epigallocatechin gallate or epicatechin gallate was reported by Durgo et al [36] at 48 but not 72 h. At more reasonable concentrations, the results are mixed: decreases in UV(B)-induced SBs [70] and cyclobutane pyrimidine dimers [72]; decreases in H 2 O 2 -induced SBs and MN [74]; a decrease in SBs induced by cumene hydroperoxide [75]; but SBs and Fpg-sites increased in tetradecanoyl phorbol acetate (TPA)-stimulated neutrophils [78] and an increase in SBs with ellagic acid in prostate cancer cells was reported by Vanella et al [73] at concentrations of 9 μM in one of the cell lines but higher concentrations in two other lines.…”
Section: Isolated Phytochemicalsmentioning
confidence: 84%
“…In addition, a prevention of DNA damage, for example attenuated cyclobutane pyrimidine dimers formation, and prevention of cell apoptosis could be observed [31,38,39]. The pre-treatment of HaCaT keratinocytes with polyphenols or phenolic extracts leads to a decreased intracellular ROS formation, induced by UVB or hydrogen peroxide.…”
Section: Protection Against Uv Damages and Oxidative Stressmentioning
confidence: 99%
“…Pang et al (31) revealed that CGA may prevent acetaminophen-induced liver oxidative stress injury via the regulation of cytochrome P450 metabolism enzymes and certain important anti-oxidant signal molecules, including proteins from the peroxiredoxins family. Cha et al (32) demonstrated that CGA reduced UVB-mediated oxidative stress in human HaCaT keratinocytes. The preventive effect of CGA with regards to VSMC damage and inhibition of Iso-induced DNA damage may have important implications in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%